2021
DOI: 10.2991/aebmr.k.210507.045
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of IFRS 16 (PSAK 73) Implementation on Key Financial Ratios: An Evidence from Indonesia

Abstract: IFRS 16 was issued to overcome the criticism of IAS 17, especially regarding the fact that many lease transactions on lessee are not included in the statement of financial position (off-balance-sheet), making it difficult for users to get an accurate view of the assets and liabilities of the leasing company, as well as being difficult to estimate the amount that is off-balance-sheet. After the adoption of this standard, companies with significant operating leases are likely to experience an increase in assets,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
1
3
0
5
Order By: Relevance
“…In contrast, the inflation rate (INFR) has a negative and statistically insignificant connection with the PER, with a coefficient of -0.046, and is positive when the control variable is taken into account. The findings of the study were found to be in line with the findings of previous investigations Silvana, Valerico, Daniel & Federico [31]; Susanti, Sufiyati & Dewi [34]; Diaz, Hernandez & Voicila [14]; Bello, Ahmad & Al-Mustapha [9]. On the contrary, the findings of Musa [45] and Bontas [8], both of which reported detrimental impacts, were found to be contradictory with the findings of the study.…”
Section: Discussion Of Findingssupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast, the inflation rate (INFR) has a negative and statistically insignificant connection with the PER, with a coefficient of -0.046, and is positive when the control variable is taken into account. The findings of the study were found to be in line with the findings of previous investigations Silvana, Valerico, Daniel & Federico [31]; Susanti, Sufiyati & Dewi [34]; Diaz, Hernandez & Voicila [14]; Bello, Ahmad & Al-Mustapha [9]. On the contrary, the findings of Musa [45] and Bontas [8], both of which reported detrimental impacts, were found to be contradictory with the findings of the study.…”
Section: Discussion Of Findingssupporting
confidence: 91%
“…Susanti, Sufiyati, and Dewi [34] investigated the impact of IFRS 16 implementation on selected Indonesian companies' key financial ratios. The research focused on the impact of airline operational performance and lease financing on the financial situation of airline operators, as well as the impact on their return on equity (ROE) and return on assets (ROA) based on total earnings.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the perspective of normative accounting theory is that it can predict management's decisions, with regard to accounting policies, to maximise their own best interests (Nasution et al 2020). Furthermore, the normative accounting theory guides policymakers on what should be done, based on theoretical principles (Susanti et al 2021). Within this research, the possible characteristics of IFFs are identified, which could enhance financial reporting transparency, while discouraging IFFs.…”
Section: Theoretical Lens Of This Workmentioning
confidence: 98%
“…Proksi ROE mengikuti proksi yang digunakan oleh (Safitri, Lestari, and Nurhayati 2019;Nomorissa and Lindrawati 2021;Rahmawati 2021). Proksi ROA mengikuti proksi yang digunakan oleh (Safitri, Lestari, and Nurhayati 2019;Nomorissa and Lindrawati 2021;Rahmawati 2021;Susanti et al 2021). Pengujian hipotesis dalam penelitian ini dilakukan dengan uji beda paired sample t-Test atas variabel-variabel penelitian dengan menggunakan data sampel yang saling berpasangan.…”
Section: Metode Penelitianunclassified